2006
DOI: 10.1111/j.1439-0434.2006.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Clonostachys rosea and Trichoderma spp. as Potential Biocontrol Agents to Pesticides

Abstract: Clonostachys rosea 47 (CR47), Trichoderma atroviride 59 (TA59), T. atroviride 312 (TA312), Trichoderma harzianum 24 (TH24), Trichoderma longibrachiatum 9 (TL9), T. longibrachiatum 144 (TL144) and Trichoderma viride 15 (TV15) were tested to evaluate their in vitro sensitivity towards five fungicides (carboxin, guazatine, prochloraz, thiram and triticonazole) and four herbicides (chlorsulfuron, chlorotoluron, flufenacet and pendimethalin). All antagonists showed low sensitivity to carboxin and thiram and high se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Ekundayo (2002) found that Thiram depressed the fungal population by one order of magnitude. Roberti et al (2006) reported that mycelial growth and conidial germination of different Trichoderma species had a broad range of sensitivity to Thiram. Mohamed (2009) reported a fluctuating effect of herbicide Oxyfluorfen on soil fungal populations.…”
Section: Resultsmentioning
confidence: 99%
“…Ekundayo (2002) found that Thiram depressed the fungal population by one order of magnitude. Roberti et al (2006) reported that mycelial growth and conidial germination of different Trichoderma species had a broad range of sensitivity to Thiram. Mohamed (2009) reported a fluctuating effect of herbicide Oxyfluorfen on soil fungal populations.…”
Section: Resultsmentioning
confidence: 99%
“…C. rosea seems to be insensitive to herbicides, according to the results we obtained and the nding that the mycelial growth of isolate CR47 was stimulated in the presence of four herbicides applied at eld dose. 21) In eld experiments, weed control in the plot borders was achieved with glyphosate, and the e ciency of C. rosea in controlling strawberry gray mold was not reduced. 9) Under eld conditions, it is expected that there will be little contact between C. rosea and herbicides due to the main targets of herbicide (soil) and biocontrol agents (aerial plant parts).…”
Section: Discussionmentioning
confidence: 99%
“…14,[17][18][19][20] For instance, the isolate C47 of C. rosea was highly sensitive to prochloraz, slightly sensitive to carboxin and thiram, and insensitive to guazatine and triticonazole. 21) Fungi di er in their sensitivity to pesticides of the same chemical class or same mode of action, 16) and we cannot generalize regarding the sensitivity of a species to a pesticide. us, research on the sensitivity of biocontrol agents to pesticides is important.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, C.rosea was also reported to decrease the infection rate caused by Fusarium graminearum in soybean plant, showing a mycoparasitic habit (Pan et al, 2013). Integration of pesticide with C. rosea and Trichoderma spp were also reported to effectively control wheat foot rot caused by Fusarium cumorum [43].…”
Section: Molecular Identities Of Potential Endophytic Fungi Based mentioning
confidence: 99%